1980
DOI: 10.1111/j.1432-1033.1980.tb04402.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Interactions between Immobilized Lysine Residues and Oligomers of Thymidylic and Deoxyadenylic Acids

Abstract: Two groups of crosslinked polyacrylic gels with immobilized lysine and lysine peptides (Lys)~ and ( L y~)~-P r o have been used as models for the chromatographic investigation of lysine-peptide -oligonucleotide interactions. One group carries carboxylic groups in addition to the peptide residues in the gel matrix; the other gel type contains no such carboxylic groups in the gel matrix.Nucleotides of the series (dT)2-5, p(dT)l -4, p(dT)l -4p, (dA)2 -5 , p(dA)1-5 and p(dA)1-4p were chromatographed on these gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a study of the interaction between mononucleotides and poly-lysine or poly-arginine peptides, electrostatic attractions were shown to be the initial force governing the interaction which, at a high concentration of the nucleotide, led to positioning and adsorption of the nucleotide base along the polyamino acid chain. 28,29 Underscoring the importance of charge around the target lysine, we showed that a highly basic 12-mer peptide of H2A, residues 3-14, was readily biotinylated at all three Lys residues in the presence of bio-5 0 -AMP, whereas the neutral p-67 peptide, residues 660-679, containing two Lys residues, one the target Lys for in vivo biotinylation, was only trace biotinylated in the absence of enzyme. These results mimic the response of fulllength H2A, which was rapidly biotinylated nonenzymatically on the N-terminal tail, when compared with BCCP which was minimally labeled after an overnight incubation.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of the interaction between mononucleotides and poly-lysine or poly-arginine peptides, electrostatic attractions were shown to be the initial force governing the interaction which, at a high concentration of the nucleotide, led to positioning and adsorption of the nucleotide base along the polyamino acid chain. 28,29 Underscoring the importance of charge around the target lysine, we showed that a highly basic 12-mer peptide of H2A, residues 3-14, was readily biotinylated at all three Lys residues in the presence of bio-5 0 -AMP, whereas the neutral p-67 peptide, residues 660-679, containing two Lys residues, one the target Lys for in vivo biotinylation, was only trace biotinylated in the absence of enzyme. These results mimic the response of fulllength H2A, which was rapidly biotinylated nonenzymatically on the N-terminal tail, when compared with BCCP which was minimally labeled after an overnight incubation.…”
Section: Discussionmentioning
confidence: 97%
“…The acryloyl peptides obtained according to method (1) are very pure and can be characterized, e.g., with 1Hor W-nmr spectroscopy. By using method (2) and (3) the peptides are obtained in almost quantitative yield and are pure enough for copolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…This determination is based on measurement of the retardation of dissolved oligonucleotides on immobilized amino acids or oligopeptides. [1][2][3] Now we are interested in the Arg-Glu-Lys sequence in which an acidic amino acid is placed between two basic residues. This sequence, as well as Arg-Glu and Glu-Arg sequences, are found in proteins such as the lac and A repressor4p5 and also in several ribosomal proteins.…”
Section: Introductionmentioning
confidence: 99%